2013
DOI: 10.1080/14697688.2012.727015
|View full text |Cite
|
Sign up to set email alerts
|

An extension of Davis and Lo's contagion model

Abstract: : The present paper provides a multi-period contagion model in the credit risk field. Our model is an extension of Davis and Lo's infectious default model. We consider an economy of n firms which may default directly or may be infected by other defaulting firms (a domino effect being also possible). The spontaneous default without external influence and the infections are described by not necessarily independent Bernoulli-type random variables. Moreover, several contaminations could be required to infect anoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…. , 1 N (t k , t k+1 ) follows a multivariate binomial distribution (see Davis and Lo [2001], Cousin et al[2012]) with correlation equal to R(t k , t k+1 ):…”
Section: The Multivariate Casementioning
confidence: 99%
“…. , 1 N (t k , t k+1 ) follows a multivariate binomial distribution (see Davis and Lo [2001], Cousin et al[2012]) with correlation equal to R(t k , t k+1 ):…”
Section: The Multivariate Casementioning
confidence: 99%
“…For analysing a systemic crisis we found that T = 7 years is a reasonable choice. The contagion mechanism is particularly intuitive and simple: the default of one node increases the probability of default of the neighbouring nodes in subsequent time steps [44][45][46][47] according the characteristics of the network of exposures {a ij }. In particular, a node i experiences an impact I i (t) at time t:…”
Section: Merging the Two Approaches: The Pd Model Frameworkmentioning
confidence: 99%
“…Very recently, we learned of the results in [3], where the idea of studying the decay of ∞ m=n P(E m ) combined with metastability appears, although not in the context of a systematic study of the moments of O. Moreover, recent applications of the overlap statistic, which include the Schutte-Nesbitt formula and moments of the overlap statistic in special cases, are found in information theory and finance [4,5,17]. In the probability textbooks the Borel-Cantelli Lemmas appear essentially unchanged without taking advantage of the fine information in the Schuette-Nesbit formula [30], see for example [6,11,21,26,35,36,47].…”
Section: Introductionmentioning
confidence: 99%